Profile of paritaprevir/ritonavir/ombitasvir plus dasabuvir in the treatment of chronic hepatitis C virus genotype 1 infection - Smith MA; Lim A (Dove Medical Press, 2015)
Michael A Smith, Alice LimDepartment of Pharmacy Practice and Pharmacy Administration, Philadelphia College of Pharmacy, University of the Sciences, Philadelphia, PA, USAAbstract: Over the last several years, many advances have been made in the treatment of chronic hepatitis C virus (HCV) infection with the development of direct-acting antivirals. Paritaprevir/ritonavir/ombitasvir with dasabuvir (PrOD) is a novel combination of a nonstructural (NS) 3/4A protein inhibitor boosted by ritonavir, an NS5A protein inhibitor, and an NS5B nonnucleoside polymerase inhibitor. This review aims to discuss the pharmacology, efficacy, safety, drug interactions, and viral drug resistance of PrOD in the treatment of HCV genotype 1 infections. Phase I, II, and III human and animal studies that describe the pharmacology, pharmacokinetics, efficacy, and safety of PrOD for HCV were identified and included. Studies that evaluated patients without cirrhosis (n=2,249) and with cirrhosis (n=422) demonstrated that PrOD for 12 or 24 weeks was effective at achieving sustained virologic response rates (>90%) in patients with genotype 1a or 1b HCV infection. Although indicated for the treatment of HCV genotype 1 infection, PrOD is also recommended for the treatment of HCV in patients coinfected with HIV. Additionally, promising data exist for the use of PrOD in liver-transplant recipients. The most common adverse drug events associated with PrOD included nausea, pruritus, insomnia, diarrhea, asthenia, dry skin, vomiting, and anemia. The high efficacy rates seen coupled with a favorable side effect profile seen with PrOD with or without ribavirin have led to its addition as a recommended treatment regimen for HCV genotype 1 infection.Keywords: direct-acting antiviral, interferon-free, ribavirin-free